User-friendly Guidelines for Tax & Statutory Management in India - Jain, Arjita; Ponde , Sandeep (Gyan Management Journal, 2018)
According to Economic Survey 2015-16 the proportion of economically active population (15-59  years J has increased from 57. 7 % to 63.3 % during the 1991-2013 periods. The employment growth in  the organized sector (public and private combined) increased by 2 %. Though huge numbers of people  are working in India and they are paying their regular taxes by consulting financial experts but many of  them are completely blank about the working and calculation of this part of their income. Considering  this we decided to work on this topic and prepare user{riendly guidelines which can be referred by  anyone. Examples have been cited for tax calculation related to salary. From the start to end process of  the salary with taxation and statutory deduction will definitely help the working professionals to  understand their own tax deductions and reduce their dependency on financial consultants.
Keywords: Tax; Statutory Management; Income Tax Return; Income Tax Forms; TDS (Taxes Deducted atSource